Bonsoir,
[tex]Conjoncture:\ \\\\
\boxed{u_n=2n^2+3n+2}\\\\
u_1=u_0+4*1+1\\\\
u_2=u_1+4*2+1=u_0+4*2+4*1+1+1=u_0+4(2+1)+2*1\\\\
u_3=u_2+4*3+1=u_0+4*(3+2+1)+3*1....\\\\
u_n=u_0+4*(n+(n-1)+....+2+1)+n*1\\\\
=2+4* \dfrac{n*(n+1) } {2} +n\\\\
=2+2*(n^2+n)+n\\\\
=2n^2+3n+2\\\\
[/tex]
Démonstration:
Initialisation
[tex]u_0=2*0^2+3*0+2=2[/tex]
On suppose vrai pour n et on démontre que c'est vrai pour n+1.
[tex]u_n=2n^2+3n+2\\\\
u_{n+1}=u_n+4n+1=2n^2+3n+2+4n+1\\\\
=(2n^2+4n+2)+3n+4+1\\\\
=2(n+1)^2+3(n+1)+2.\\\\
[/tex]